Digital skills in enterprises according to the European digital entrepreneurship sub-indices : cross-country empirical evidence - Huđek, Ivona (Array, 2019)
Nowadays, the development of Internet technology and the effects of digital transformation are leading to the need for more skillful information and communications technology (ICT) specialists in almost every sector of the economy, in order to benefit from technological innovations. That also leads to the need for every employee to be prepared for new changes in production and service delivery processes. In this study, the factors of digital skills in enterprises that significantly affect the digital entrepreneurship start-up sub-index and digital entrepreneurship scale-up sub-index in the EU countries, are identified and the models are designed to analyse the relationships between the factors. In an increasingly digital world, where production processes and service delivery are continuously evolving, EU countries, that is, policymakers and entrepreneurs should be aware of the digital transformation and, thus, pay attention to the digital skills and provide learning opportunities and supportive environment for the workers in acquiring the new skills and knowledge.